Combining spatial ecology and economics to incorporate recreational fishing into marine spatial planning. (20th December 2021) - Navarro, Matthew; Hailu, Atakelty; Langlois, Tim; Ryan, Karina L; Burton, Michael; Kragt, Marit E
Abstract: Many researchers have pointed to coastal environments and their use for energy production, aquaculture, and conservation as key to solving profound challenges facing humanity. Navigating this transition in ocean space necessitates tools to quantify impacts on displaced marine users, including recreational fishers. In this study, we present a novel method combining spatial ecological models of recreational catch with fine-scale random utility models of site choice to predict the impacts of site closures on recreational fishing experiences (fisher welfare). We demonstrate our approach by modelling data from over 10 000 fishing trips to fine-scale sites across 1500 km of coastline in the south-west of Australia and simulating the effects of no-take marine reserves recently implemented in the Australian Marine Parks. The results show how the combination of random utility modelling with spatial ecological methods provides a powerful tool for investigating recreational fisheries as joint social-ecological systems and incorporating recreational fishing into marine spatial planning.